Identification Of Strn-Ntrk2 Rearrangement In A High Grade Sarcoma, With Good Clinical Response To Firstline Larotrectinib Therapy. (28th October 2020) - Lin, R; Wang, Z; Jiang, W; Basu-Mallick, A
Abstract: Casestudy: Gene fusions involving tropomyosin receptor kinase genes, NTRK (NTRK1-3), are important in tumorigenesis. Larotrectinib, a selective NTRK inhibitor, is recently approved to treat NTRK fusion positive solid tumors. We herein report a case of soft tissue sarcoma harboring two STRN-NTRK2 gene fusions, with good clinical response to firstline larotrectinib treatment. Results: A 35 year-old female presented with pain in the right gluteal region, and a large solid mass without overlying erythema, edema and induration was identified. Initial MRI study showed a heterogenous, vascular and partially necrotic mass (16.5 x 12.9 x 10.4 cm) centered in the right gluteus medius and maximus muscles. A core biopsy of the mass showed a cellular mesenchymal neoplasm with round/ovoid cells, high mitosis (21 per 10 HPFs) and focal staghorn type vessels, reminiscent of solitary fibrous tumor. However, STAT6 immunostaining was negative. Additional immunostains show no specific lineage. Our in-house NGS fusion panel showed two in-frame STRNNTRK2 fusions, containing the same 5' partner sequence (exon 1-3) of STRN, with the 3' fusion partner starting from either the exon 15 or the exon 16 of NTRK2. Due to the large size and location of the tumor, larotrectinib was initiated as firstline therapy. The patient noticed a quick amelioration of tumor related pain, and a significant shrinkage of the size of tumor following the initial 7-day treatment. On post-treatment day 52, MRI showed the tumor significantly decreased in size to 7.7 x 7.4 x 6.6 cm with satisfactory symptomatic relief. Conclusion: NTRK2 fusions are relatively rare when compared with NTRK1 and NTRK3, especially in sarcoma. Of note, the only other report in the literature of NRTK2 fusion- positive sarcoma also showed SFT-like morphology, and the patient responded well to larotrectinib as second line therapy.